Legal Standing of Beneficial Ownership Under Nominee Agreements in Indonesian Corporate Law - Kadek Wijana; I Nyoman Sujana; Ni Komang Arini Styawati (Jurnal Smart Hukum (JSH), 2027)
The absence of explicit legal regulation concerning beneficialownership within Indonesian corporate law has generateduncertainty regarding the legal position of investors operatingthrough nominee agreements. This study examines the legal standing of beneficial ownership and its legal consequences withinnominee arrangements involving domestic limited liabilitycompanies in Indonesia. Normative legal research was employedusing statutory, conceptual, and case approaches to examine theinteraction between the Company Law, the Investment Law, theCivil Code, and related regulations governing beneficialownership. The analysis demonstrates that Indonesian corporatelaw recognizes only registered shareholders as holders ofcorporate rights, whereas beneficial owners remain confined toadministrative recognition without acquiring enforceable civillegal standing. Nominee agreements established to conceal theidentity of the actual investor are inconsistent with the objectiverequirements of lawful contracts under Articles 1320 and 1337 ofthe Civil Code and constitute fraus legis, rendering suchagreements legally void and incapable of creating valid shareholder rights. Consequently, beneficial owners cannoteffectively enforce corporate rights or contractual claims whendisputes arise with nominees. The novelty of this study lies in integrating corporate, investment, and contract law to explain thenormative inconsistency governing beneficial ownership andproposing regulatory harmonization to strengthen legal certainty, investor protection, and corporate governance. Future studies maycomparatively examine beneficial ownership regulation acrossdifferent jurisdictions to support legislative reform in Indonesia.